A contribuição das capacidades dinâmicas no processo da escalabilidade da inovação social : o caso do protocolo comunitário em comunidades ribeirinhas - Facco, Ana Luíza Rossato (Universidade do Vale do Rio dos Sinos, 2022)
Scaling social innovation happens when an initiative expands its operations to another context, modifies existing regulations, policies, and rules, and changes the culture and customs of a society. However, there are major barriers related to scaling a social innovation, especially in regions characterized by institutional voids. In the face of these challenges, the Dynamic Capabilities theoretical lens and its Microfoundations adapted to the social context can contribute to and support the process of scaling social innovations. In this regadr, this thesis has the main objective of understanding the contribution of Dynamic Capabilities to the scalability of Social Innovation in initiatives developed in remote regions of Brazil characterized by institutional voids. Through a case study in a remote territory of Brazil located in the State of Amapá, with difficult access and precarious infrastructure where Traditional Peoples and Communities live. This territory scaled a methodology of social innovation as a way of developing its territory and overcoming social problems. Aiming to understand how this process took place, this PhD dissertation used the qualitative research method with a scientific approach considered exploratory, using an interpretive paradigm based on this single case study. Data collection consisted of online interviews with different local actors and supplemented by documents. Content analysis was used to analyze the data, resulting in four methodological steps. Among the main results, the theoretical contribution of capabilities in the scaling social innovation stands out, constituting the first theoretical contribution of this thesis: to demonstrate a set of Dynamic Capabilities and specific Microfoundations that were necessary to scale a methodology of social innovation in the context of traditional communities, demonstrating endogenous and exogenous social practices, these results demonstrate that Dynamic Capabilities and their Microfoundations constituted the operationalization of the scalability process. Furthermore, Dynamic Capabilities were the orchestration of a set of endogenous and exogenous social practices resulting in the development of the territory. This thesis further advances the theory by identifying four dimensions, specifically by including the educational dimension as an important element to analyze the development of a territory characterized by institutional voids. Another highlight was the last theoretical contribution demonstrating that the concept of social innovation goes beyond a new social practice, validating the inclusion of process and result logic, proving to be a concept with an integrated view of practice, process, and result.
Keywords: Escalabilidade da inovação social; Capacidades dinâmicas; Povos e comunidades tradicionais; Vazios institucionais; Scaling social innovation; Dynamic capabilities; Traditional peoples and communities; Institutional voids; ACCNPQ::Ciências Sociais Aplicadas::Administração